The Spirit of Praise Music and Worship in Global Pentecostal-Charismatic Christianity - Althouse, Peter; Boone, Will; Evans, Mark; Gladwin, Ryan; Ingalls, Monique M.; Ingalls, Monique; Johnson, Birgitta; Kidula, Jean; Klaver, Miranda; Mall, Andrew; Marshall, Kimberly; McCoy, Andrew; et al. (Penn State University Press, 2021)
In The Spirit of Praise, Monique Ingalls and Amos Yong bring together a multidisciplinary, scholarly exploration of music and worship in global pentecostal-charismatic Christianity at the beginning of the twenty-first century. The Spirit of Praise contends that gaining a full understanding of this influential religious movement requires close listening to its songs and careful attention to its patterns of worship. The essays in this volume place ethnomusicological, theological, historical, and sociological perspectives into dialogue. By engaging with these disciplines and exploring themes of interconnection, interface, and identity within musical and ritual practices, the essays illuminate larger social processes such as globalization, sacralization, and secularization, as well as the role of religion in social and cultural change. Aside from the editors, the contributors are Peter Althouse, Will Boone, Mark Evans, Ryan R. Gladwin, Birgitta J. Johnson, Jean Ngoya Kidula, Miranda Klaver, Andrew Mall, Kimberly Jenkins Marshall, Andrew M. McCoy, Martijn Oosterbaan, Dave Perkins, Wen Reagan, Tanya Riches, Michael Webb, and Michael Wilkinson